A NOVEL APPROACH TO ESTIMATING HEMODYNAMICS IN THE ARTERIAL PORTION OF THE VASCULATURE - V. S. Zadionchenko; S. S. Suvorova (Российский кардиологический журнал)
A novel approach to estimating hemodynamics in the arterial portion of the vasculature.